The Changing Distribution of the Male Ethnic Wage Gap in Great Britain - Ken Clark; Steve Nolan (Institute of Labor Economics (IZA), 2021)
We decompose the ethnic pay gap in Great Britain across the distribution of hourly wages, yielding a detailed insight into differences between groups and how these vary over pay percentiles and through time. While some groups experience reductions in the pay gap consistent with lower discrimination, including relatively well paid Indian workers and relatively poorly paid Bangladeshis, others - specifically Black groups - face an apparent glass ceiling barring access to well paid jobs. The increasing educational attainment of Britain's ethnic groups provides some optimism around narrowing pay differentials, particularly at the top of the distribution, while the introduction and uprating of the National Minimum/Living Wage has contributed to improvements at the lower end.
Keywords: D31; J15; J31; J38; 330; ethnic pay gap; race discrimination; minimum wages; decomposition